Analysis of the Relationship between Micro, Small and Medium Enterprises Sharia Compliance with Increasing Leverage on the Impact of Covid-19 (Case Study of MSMEs in Bandung City, Indonesia) - Nurhayati, Nurhayati; Suntana, Ija (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
The purpose of this study was to identify the importance of shari'a compliance in the context of MSMEs, MSME's reputation, access to funding, and the impact on the role of shari'a compliance during increased leverage, to determine whether shari'a compliance is associated with increased leverage in MSMEs. is to analyze the impact discussed. This study takes a descriptive-analytical approach to verificative how Shariah compliance affects MSMEs' ability to utilize resources. Primary data sources and the technique for collecting data in this research uses a questionnaire technique. The analysis used in this research is likert scale analysis, hypothesis testing design using confirmatory factor analysis is a method of one of the multivariate analysis methods part of SEM (Structural Equation Modeling) whose function is to confirm or test the model to be hypothesized. To test the hypothesis model, this research uses the outer model for the measurement model and the inner model for the structural model. The Micro, SME population of Islamic Banking customers is his 156 companies and consists of his sample of 50 respondents using non-probability sampling. The study found a correlation and impact between Shariah compliance and leverage in MSMEs in Bandung. Findings from the study highlight the application of Shariah principles in the business activities of MSMEs, in particular the ban on Riba, transparency and fairness, social and environmental responsibility, and resilience to challenges in applying Shariah elements to their business activities. is shown. Shariah compliance impacts MSMEs' reputation, investor confidence, and access to finance